The drivers of US banks’ demand of government securities - Ferreira, Carlos Alberto Piscarreta Pinto (2024)
We use individual bank balance sheet data to investigate those bank-specific characteristics that are relevant to explain US banks’ demand of two groups of government securities: Agencies and Treasuries. We conclude that some drivers but not all are common. Higher holdings are associated with poorer loan portfolio quality in both cases. Agencies also respond positively to lower margins, a contracting economic cycle, sub-par regional dynamics and less clearly higher business cycle risk. Treasuries alone are positively impacted by the erosion of the capital position. Variables such as the loan rate spread, past profitability, or income diversification fail to be significant. We find no direct impact of unconventional monetary policy in Agencies and the impact on Treasuries seems time-bounded and bank entity specific. Our finding suggest that it will be mainly up to other investors than banks to replace the Fed as it reduces its balance sheet.